Functioning of the Verb tăjtɨ in Kazym and Shuryshkar Dialects of Khanty; International Journal of Languages, Literature and Linguistics (IJLLL); Vol. 4, iss.3 - Vorobyeva V. V. Viktoriya Vladimirovna (2018, 2018)
Title screen